2004
DOI: 10.1249/01.mss.0000132375.00721.7a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ski Binding Parameters on Knee Biomechanics: A Three-Dimensional Computational Study

Abstract: A binding with two pivot points, one positioned in front and the other at the back, could sense twist loads applied to the ski both at the front and at the back, and might, therefore, be a solution to reduce the occurrence of ACL injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…Our results indicate that nonrigid ankle taping provides some protective benefits to the knee during running and cutting through a reduction in internal rotation and varus moments and varus impulse. This refutes our initial hypothesis that ankle constraint would increase knee joint loading, a premise which was developed on the basis of the results from ski-boot testing (29,38) and the lack of consensus from analysis of landing tasks undertaken with ankle bracing (19,24,40). Our results do, however, correspond with those of previous research using ankle bracing during dynamic athletic tasks, which have also demonstrated positive outcomes for knee joint loading.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our results indicate that nonrigid ankle taping provides some protective benefits to the knee during running and cutting through a reduction in internal rotation and varus moments and varus impulse. This refutes our initial hypothesis that ankle constraint would increase knee joint loading, a premise which was developed on the basis of the results from ski-boot testing (29,38) and the lack of consensus from analysis of landing tasks undertaken with ankle bracing (19,24,40). Our results do, however, correspond with those of previous research using ankle bracing during dynamic athletic tasks, which have also demonstrated positive outcomes for knee joint loading.…”
Section: Discussionsupporting
confidence: 61%
“…Despite the effectiveness of ankle tape in reducing the likelihood and severity of sprain-type injuries, unnatural constraint of the ankle may increase the risk of injuries to proximal joints such as the knee. Studies of ski-boot performance suggest that tall stiff boots afford excellent protection to the ankle but may contribute to knee injuries through boot-induced anterior drawer during a fall (29,38). Although ankle tape is much less stiff than a ski boot, altered knee joint kinematics during simple tasks performed with nonrigid ankle bracing has been observed (36).…”
mentioning
confidence: 99%
“…25,26,59,60 At initial contact from a jump, ankle bracing increased knee flexion. 26 However, the increased knee flexion was not associated with an increase in knee-injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a change in the shape of the skis can lead to changes in the skiing style, which may make skiers adopt knees positions that are more likely to result in injury. Since the advent of carving skis in 1999, there has been much debate on how this change would theoretically increase knee injuries [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . However, there have been no evalu-of the Department of Orthopedic Surgery, Showa University Niigata Prefecture, Japan .…”
Section: Introductionmentioning
confidence: 99%